Macro-financial linkages between emergent and sustainable economies in a context of the European sovereign debt crisis - Ferreira, Nuno (Archives of Business Research, 2018)
The aim of the study is to identify the international economic linkages between European emergent countries and different economies under the European sovereign debt crisis from the 1990s through 2015. More precisely, we compared the worst-performing European economies with more economically sustainable economies (such France, Germany, the United Kingdom and Norway). Switzerland, China, Japan and the United States were also included to evaluate the external impacts on the European Union. To examine the increasing macro-financial linkages, their interactions were included in the Global VAR model. Credit variables and oil were used to analyse international transmission of the Euro area along with the US, China, Japan and Switzerland credit and aggregate demand shocks. The model was set up with quarterly data from a sample of 11 countries, and the followed global economic variables that included: Real GDP, inflation, real equity prices, real exchange rates, government bonds (10 year), interest rates (3 month) and the price of oil. The results showed that the US influence was contracted since all macroeconomic variables did not react significantly with the oil and US long-term interest rate shocks.